Pengaruh Biaya Pendidikan, Kualitas Pelayanan Akademik, dan Sarana Prasarana Terhadap Kepuasan Siswa pada SMA PAB 8 Saentis - Arfiansyah, M. Dimas; Tanjung, Yahya (Education Achievement: Journal of Science and Research, 2025)
The decision to stay overnight is one of the consumer's actions in choosing or using accommodation services which is determined from the start with several factors that influence this decision. This research aims to determine and analyze the influence of promotions, discounts and facilities on the decision to stay at the Grand Darussalam Hotel Medan. The method in this research uses quantitative methods. The number of samples in this research was 100 respondents. The data collection technique in this research uses a questionnaire. The sample size was drawn using a simple probability sampling formula. Data management uses SPSS version 25 software. Based on the results of this research, Promotion (X1) has a positive and significant influence on the decision to stay, Discounts (X2) do not have a significant positive influence on the decision to stay and Facilities (X3) have a positive and significant influence on the decision to stay. decision to stay.